If x = 2 , 4 are the solutions of the equation ∣ m x + α ∣ + ∣ m x + β ∣ = c where m > 0 and α , β , c are non zero constants , then ∣ m α + β ∣ is equal to
Also check this Optics Problem
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
W h e n x = 2 , w e h a v e , ( 2 m + α ) + ( 2 m + β ) = c , a n d ( 2 m + α ) − ( 2 m + β ) = c . S u b t r a c t i n g t h e f i r s t e q u a t i o n f r o m t h e s e c o n d w e g e t 2 m = − β . . . . . . . . . . . . ( A ) S i m i l a r l y f o r x = 4 , w e g e t 4 m = − α . . . . . ( B ) S o l v i n g ( A ) a n d ( B ) , w e g e t 6 m = − ( α + b e t a ) . ⟹ ∣ ∣ ∣ m α + β ∣ ∣ ∣ = 6 . N o t e t h a t s o l v i n g a b s v a l u e s , w e g e t f o u r e q u a t i o n s b u t p a i r s o f t w o s a r e i d e n t i c a l . e . g . ∣ a + b ∣ + ∣ a − b ∣ = 0 , g i v e s 2 a = 0 , . . . . 2 b = 0 , . . . . − 2 a = 0 , . . . . − 2 b = 0 S i n c e t h e e q u a t i o n i s e q u a l t o 0 , a n d 0 = − 0 , f i r s t a n d T h i r d a n d s e c o n d a n d f o u r t h e q u a t i o n s a r e i d e n t i c a l .
Problem Loading...
Note Loading...
Set Loading...
|x+alpha ÷m|+|x+beta÷m|=c÷m (since m>0) draw graph. x coordinate of Midpt of (2,c÷m) and (4,c÷m) is same as that of (-alpha÷m,0) and (-beta÷m,0) . so answer =6